An innovative use of PIRS technique for pediatric femoral hernia: report of 2 cases - Ergun Ergun; Yusuf Alper Kara; Beytullah Yagiz; Sila Ispir Karalar; Ozlem Balci; Ismet Faruk Ozguner (SpringerOpen, 2022)
Abstract Background Femoral hernia is very rare in children. Surgical intervention is necessary for treatment. There are many different surgical methods explained before. Laparoscopic single port repair technique is not reported before. Case presentation A 2.5-year-old girl with left femoral hernia and a 5.5-year-old boy with a right femoral hernia were presented to the hospital with bulging on the groin. Using a 5-mm telescope with optical forceps, the defects of patients were repaired with percutaneous ring suturing technique via spinal needle without excision of the lipoma. No complications developed on the patients in 12 months follow-up. Conclusion Laparoscopic single port needle assisted repair is a safe and feasible method repairing femoral hernia and excision of the lipoma should be kept in mind to avoid possible recurrences.